Metabolism Score for Visceral Fat (METS-VF): A New Predictive Surrogate for CKD Risk - Feng L; Chen T; Wang X; Xiong C; Chen J; Wu S; Ning J; Zou H (Diabetes, Metabolic Syndrome and Obesity, 2022)
Ling Feng,1,2,* Tong Chen,3,* Xuan Wang,1 Chongxiang Xiong,1,4 Jianhui Chen,1 Shiquan Wu,3 Jing Ning,3 Hequn Zou1,3 1Department of Nephrology, The Third Affiliated Hospital, Southern Medical University, Guangzhou, People’s Republic of China; 2Department of Nephrology, Shenzhen Hospital, Southern Medical University, Shenzhen, People’s Republic of China; 3Department of Nephrology, South China Hospital of Shenzhen University, Shenzhen, People’s Republic of China; 4Department of Nephrology, The First Dongguan Affiliated Hospital of Guangdong Medical University, Dongguan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hequn Zou, Department of Nephrology, The Third Affiliated Hospital, Southern Medical University, 183, Zhongshan West Avenue, Tianhe District, Guangzhou, 510630, People’s Republic of China, Email Hequnzou@hotmail.comPurpose: Metabolic disorders are closely related to the occurrence and development of chronic kidney disease (CKD). We explored the prospective association between the Metabolic Score for Visceral Fat (METS-VF) and CKD in a 5-year follow-up study.Patients and Methods: In this cohort study, 631 adults not suffering from CKD from Wanzhai Town, in China in 2012 were included at baseline and followed up in 2017 and 2018. Multivariable logistic regression was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for the association between METS-VF and CKD risk. Area under the receiver operating characteristic curve (AUC) analyses were used to evaluate the ability of METS-VF, waist-to-height ratio (WhtR), visceral adiposity index (VAI), homeostatic model assessment of insulin resistance (HOMA-IR), body mass index (BMI) to predict CKD risk.Results: We identified 103 CKD cases during follow-up. After adjustment for confounding factors, comparing the lowest quartile of METS-VF, the OR (95% CI) of CKD risk in the highest quartile was 3.04 (1.39– 6.64). The per Standard deviation (SD) increase in METS-VF was positively correlated with CKD risk. The AUC of METS-VF for predicting CKD risk was, in general, higher than that for WhtR, VAI, HOMA-IR, and BMI.Conclusion: METS-VF may be an indicator for predicting CKD risk.Keywords: CKD, METS-VF, visceral obesity